Evaluation of Acute Toxicity (LC50) and Biochemical Response of Labeo rohita (Hamilton 1822) to Crystal Violet Dye Exposure - Dhandale, Archana B.; Patil, Sachinkumar. R.; Manjare, Surat. A. (Asian Journal of Biological and Life Sciences)
Background: Crystal Violet (CV) dye has been widely used in dye processing industries and also used to provide a deep violet colour to paints and printing ink. It is a topical antimicrobial agent that inhibits cell replication, it can be toxic if swallowed and used in various staining procedures. CV has been reported as a recalcitrant dye molecule, a mitotic poison that persists in environment for a long period and pose toxic effects in environment especially aquatic biome. Fishes are best indicator of water quality and are used for ornamental and food purpose. In the present study, the freshwater fish, Labeo rohita fingerlings, were exposed to CV dye and Biochemical changes were recorded (protein, glycogen and lipid). Materials and Methods: In the present study Lethal Concentration (LC50) of CV on Labeo rohita at 96 hr was determined by using SPSS. Biochemical analysis of tissues like liver, gill, intestine and kidney was done through protein estimation by Lowry’s method, glycogen estimation by DeZwaan and Zandee method and lipid estimation by Barnes and Blackstock method. Results: The fingerlings of Labeo rohita weighing 7±0.4 g shows abnormal behaviour like hyper activity, excess mucus secretion, try to jump outside the tub, changes in swimming pattern in acute exposure, while in chronic exposure fishes become lethargic, swimming at corner and body becomes pale in colour. The total biochemical content of protein, glycogen and lipid was decreased after the exposure of acute and chronic level at significance level (p<0.01). Chronic exposure shows more decrement of biochemical composition as compare to acute (p<0.01). The observations show that CV gets easily adsorbed in fish tissue (liver, gill, kidney, intestine) from surrounding thereby reducing the metabolism of fish. Conclusion: This study shows that CV alters the total biochemical composition of fish. It also alters the behavioural response after the exposure of CV.
Keywords: Crystal violet; Toxicity; Biochemical changes; Acute; Chronic; Labeo rohita.